Spica and the annual cycle of PKS B1322–110 scintillations. Issue 3 (7th June 2019) - Bignall, Hayley; Reynolds, Cormac; Stevens, Jamie; Bannister, Keith; Johnston, Simon; Tuntsov, Artem V; Walker, Mark A; Gulyaev, Sergei; Natusch, Tim; Weston, Stuart; Md Said, Noor Masdiana; Kratzer, Matthew
ABSTRACT: PKS B1322–110 is a radio quasar that is located only 8.^′ 5 in angular separation from the bright B star Spica. It exhibits intraday variability in its flux density at GHz frequencies attributed to scintillations from plasma inhomogeneities. We have tracked the rate of scintillation of this source for over a year with the Australia Telescope Compact Array, recording a strong annual cycle that includes a near-standstill in August and another in December. The cycle is consistent with scattering by highly anisotropic plasma microstructure, and we fit our data to that model in order to determine the kinematic parameters of the plasma. Because of the low-ecliptic latitude of PKS B1322–110 , the orientation of the plasma microstructure is poorly constrained. None the less at each possible orientation our data single out a narrow range of the corresponding velocity component, leading to a one-dimensional constraint in a two-dimensional parameter space. The constrained region is consistent with a published model in which the scattering material is associated with Spica and consists of filaments that are radially oriented around the star. This result has a 1 per cent probability of arising by chance.